A Novel Inhibitor of Homodimerization Targeting MyD88 Ameliorates Renal Interstitial Fibrosis by Counteracting TGF-β1-Induced EMT in Vivo and in Vitro - Jian-Hua Liu; Long He; Zhi-Miao Zou; Zuo-Chuan Ding; Xue Zhang; Hao Wang; Ping Zhou; Lin Xie; Shuai Xing; Cheng-Zhi Yi (Karger Publishers, 2018)
Background/Aims: The TLR/MyD88/NF-κB signaling pathway has been successfully used to treat renal interstitial fibrosis (RIF). However, the exact therapeutic mechanism is still unknown. Here, we assessed the therapeutic efficacy of TJ-M2010-2, a small molecular compound that inhibits MyD88 homodimerization, in RIF induced by ischemia reperfusion injury (IRI). Methods: In vivo, RIF was induced in mice by IRI, and the mice were prophylactically treated with TJ-M2010-2. In vitro, HK-2 cells were incubated with TGF-β1 to induce EMT, and the cells were pretreated with TJ-M2010-2. Results: We found that, compared with the IRI group, the TJ-M2010-2 group showed marked attenuation of RIF and renal function injury; decreased expression of TGF-β1, α-SMA, vimentin, MMP2 and MMP9; and increased E-cadherin expression. Furthermore, TGF-β1-induced EMT was blocked by TJ-M2010-2 in HK-2 cells, as evidenced by blocked morphologic transformation, restored E-cadherin expression and inhibited α-SMA expression. In addition, compared to the TGF-β1 group, the TJ-M2010-2 group showed profound inhibition of the expression of TRAF6, p65 and Snail and upregulation of the expression of IκBα. Conclusion: This MyD88 inhibitor may be a potential therapeutic agent to ameliorate RIF.